Expert Panel consensus statements on the optimal usage of rituximab for the management of rheumatoid arthritis in India - Keerthi Talari; Vinod Ravindran; Pradip Kumar; Pravin Patil; Sarath Chandra Mouli; Syamasis Bandyopadhyay; Balebail G Dharmanand; Abhrajit Ray; Shankaralingam Rajeshwari; Sanjiv N Amin; Jyotsna Oak; Ved Chaturvedi; et al. (Indian Journal of Rheumatology)
Pharmacological management of rheumatoid arthritis (RA) includes synthetic and biological disease-modifying antirheumatic drugs (DMARDs). Biological DMARDs, also referred to as “biologics,” rapidly retard progression of the joint damage seen in RA. Rituximab is a well-established biologic for the management of RA with several biosimilar versions available. This document presents the consensus statements on the usage of rituximab for the management of RA developed by a group of 14 experienced rheumatologists from India. This expert panel identified areas of interests, collated and summarized relevant literature, developed, debated and refined and revised the statements which were voted upon at relevant stages. Subsequently, a wider consultative process including voting on the draft statements involved 18 more rheumatologists from across India. The approved final version has 28 consensus statements related to the following seven areas of rituximab therapy in RA, namely, contraindication, pretreatment screening, treatment schedule, evaluation of response, safety, and research agenda for future. It is envisaged that these consensus statements would help in optimizing the usage of rituximab in RA not only in India but also in other countries and benefit all stakeholders.